A transcription factor OsbHLH156 regulates Strategy II iron acquisition through localising IRO2 to the nucleus in rice - Wang, Shoudong (The New phytologist, 2020)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.